2005
DOI: 10.1248/cpb.53.277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Medium and Temperature on the Hydrolysis Kinetics of Propacetamol Hydrochloride: Determination Using Derivative Spectrophotometry

Abstract: Paracetamol (acetaminophen; PA) is a poorly water-soluble analgesic that is widely used in hospital and ambulatory practice for the relief of mild to moderate pain associated with headache, backache, arthritis pain, and postoperative pain.1-3) It has been used in the treatment of pain in combination with aspirin, caffeine, opiates and/or other agents. Paracetamol also has antipyretic effects that do not differ significantly from those of aspirin, although it has only weak antiinflammatory effects. 4,5) Paracet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[8][9][10] As illustrated in Scheme 1, the two routes differ primarily in the sequence in which the saccharin moiety is added to the acetyl unit. In Route A, 9,10 the saccharin moiety is added in the last step to the 2-chloroacetamide intermediate 8 that has been previously generated from 4-aminophenol (6) and 2-chloroacetyl chloride (7). This yields 3 via a two-step process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] As illustrated in Scheme 1, the two routes differ primarily in the sequence in which the saccharin moiety is added to the acetyl unit. In Route A, 9,10 the saccharin moiety is added in the last step to the 2-chloroacetamide intermediate 8 that has been previously generated from 4-aminophenol (6) and 2-chloroacetyl chloride (7). This yields 3 via a two-step process.…”
Section: Resultsmentioning
confidence: 99%
“…A water-soluble analogue of 1 is the prodrug propacetamol hydrochloride ( 2 ) 5,6. This form of acetaminophen is rapidly and completely hydrolyzed by plasma esterases to release 1 7. The pharmacological effects in clinical trials have shown that 2 possesses similar efficacy to 1 , but due to its greater water-solubility can be parenterally administered and thus can be employed when oral administration is not possible 5,6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR spectra were recorded in DMSO-d 6 using tetramethylsilane (TMS) as an internal standard with 400-MHz spectrometer. Mass spectra were recorded on an Agilent-liquid chromatography-mass spectrometry (LCMS) instrument under chemical ionization (CI) conditions and given by Q+1 values only.…”
Section: Methodsmentioning
confidence: 99%
“…A water-soluble analogue of 1 is the prodrug propacetamol hydrochloride 2 (5). This form of paracetamol is rapidly and completely hydrolysed to release 1 (6). The pharmacological effects in clinical trials have shown that 2 possesses efficacy similar to that of 1.…”
Section: Introductionmentioning
confidence: 99%